The trends and future projections of intraocular foreign bodies among children and adolescents: a global analysis - Zupeng Lu; Xindan Xing; Xindan Xing; Xindan Xing; Wen Li; Tong Qiao (Frontiers in Medicine)
ObjectiveThe aim was to evaluate the disease burden of intraocular foreign bodies (IOFBs) among children and adolescents globally based on the Global Burden of Disease, Injury, and Risk Factor Study 2021 (GBD 2021).MethodsData were extracted from the GBD 2021. The incidence and DALYs number and rate with 95% uncertainty interval (UI) and estimated annual percent change (EAPC) of IOFBs were estimated by age, sex and socio-demographic index (SDI) region. A Bayesian age-period-cohort (BAPC) analysis model was used to predict trends in the next ten years.ResultsGlobally, it is estimated that the incidence number of IOFBs among children and adolescents increased from 5842769.65 in 1990 to 6154651.76 in 2021, while the age-specific incidence rate decreased from 258.69 in 1990 to 233.50 in 2021, with a EAPC being −0.54. The 15–19 years group had the highest incidence and DALYs number, while 0–4 years group had the lowest. The projective model indicates that the burden for IOFBs will rise sharply in the next ten years.ConclusionThe global incidence and disease burden of blindness and vision loss in children and adolescents due to IOFB have shown a slight decline from 1990 to 2021. However, there may be a significant upward trend in the future, which requires the vigilant attention of policymakers.